2016
DOI: 10.1016/j.cppeds.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Social Determinants of Health Among Children and Families Living in Poverty: A Guide for Clinicians

Abstract: Approximately 20% of all children in the United States live in poverty, which exists in rural, urban, and suburban areas. Thus, all child health clinicians need to be familiar with the effects of poverty on health and to understand associated, preventable, and modifiable social factors that impact health. Social determinants of health are identifiable root causes of medical problems. For children living in poverty, social determinants of health for which clinicians may play a role include the following: child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
154
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 129 publications
4
154
0
15
Order By: Relevance
“…(30) While social risk assessment is increasingly upheld as a critical component of preventive patient care, no singular “right” way to assess (or intervene) has been established. (31, 32) Given these challenges, it is possible that area-based measures or indices could help frame or inform patient-level social histories. We previously showed significant correlations between area-level and family-reported measures of socioeconomic status within a cohort of children hospitalized with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…(30) While social risk assessment is increasingly upheld as a critical component of preventive patient care, no singular “right” way to assess (or intervene) has been established. (31, 32) Given these challenges, it is possible that area-based measures or indices could help frame or inform patient-level social histories. We previously showed significant correlations between area-level and family-reported measures of socioeconomic status within a cohort of children hospitalized with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…23,30-39 Many CHCs already try to address patients’ SDH, but their approaches to doing so have historically been manual and ad-hoc. 40-44 …”
Section: Introductionmentioning
confidence: 99%
“…Research also showed that household and neighborhood poverty are related to stress (Schulz et al., ), and the cumulative effect of stressors such as housing or food insecurity, child abuse or neglect, parental substance abuse, and violence – factors associated with poverty (Evans & English, ) – can induce a toxic stress response in young children, which can lead to long‐term changes in brain structure and function in infancy and early childhood (McEwen et al., ; Shonkoff et al., , ). Neighborhood poverty was also shown to be correlated with poor nutrition and obesity (Morland, Roux, & Wing, ), which combined with risk factors such as community violence and interpersonal and environmental trauma prevalent in areas of poverty, contribute to chronic physical and mental health problems across the life course (Chung et al., ; Curry, Latkin, & Davey‐Rothwell, ; Leventhal & Brooks‐Gunn, ; Seligman, Laraia, & Kushel, ). The structural perspective also emphasizes that the lack of access to adequate health care, particularly preventative health care, can exacerbate these problems.…”
Section: Introductionmentioning
confidence: 99%